Energy Potential of Central Asian States: Prospects for Nuclear Power Development - Osmanovna, Khalova Gyulnar; Arslanovich, Arslanov Magomed; Rakhmanovich, Bagyev Isa (International Journal of Energy Economics and Policy, 2026)
This study offers a comprehensive analysis of the pressing challenges and strategic prospects for developing the energy potential of the Central Asian region. The research begins with the acknowledgment of the region’s growing geopolitical and energy significance, which is nonetheless offset by substantial internal asymmetries. The investigation identifies a number of fundamental structural imbalances, including the stark disparity in the distribution of hydrocarbon reserves and hydropower resources, the extensive physical and moral obsolescence of generation and transmission infrastructure, systemic seasonal energy deficits, and persistent conflicts of interest over the use of transboundary waterways. A significant portion of the analysis focuses on assessing the potential of nuclear energy as a strategic instrument for overcoming electricity generation shortfalls, reducing environmental burdens, and stimulating long-term economic growth in Central Asian countries. Based on a detailed review of the national energy sectors across the region, the article outlines pathways for multilateral cooperation. The central conclusion of the analysis is that only a coordinated and strategically sound energy policy can serve as the primary driver for ensuring sustainable socioeconomic development and strengthening the sovereignty of Central Asian states amid deepening global instability.